Evaluation of the predictors of successful sperm retrieval of micro-TESE in cases with mosaic Klinefelter versus cases with non-mosaic Klinefelter: a prospective case series study - Amr Elahwany; Fatma A. Elrefaey; Hisham Alahwany; Hesham Torad; Sameh Fayek GamalEl Din; Rashad Mohammed Saeed Dawood; Mohamed Wael Ragab; Ahmed Fawzy Megawer (Basic and Clinical Andrology)
Abstract Background We evaluated the predictors of eventful microsurgical testicular sperm extraction (micro-TESE) from infertile men with Klinefelter syndrome (KS). Results The mean age of the patients was 32.4 ± 6.3 years. The mean serum levels of follicle stimulating hormone (FSH), luteinizing hormone (LH), total testosterone (TT), estradiol (E2) and prolactin were 34.38 ± 14.66, 18.92 ± 6.54, 3.18 ± 2.08, 28.2 ± 10, 11.56 ± 5.09, respectively. The mean right (Rt) testicular and left (Lt) testicular volumes were 2.17 ± 0.83 ml, 2.2 ± 0.89 ml, respectively. Mosaic KS patients showed highly significant TT compared to non-mosaic KS patients. Twenty-six patients out of 50 patients (52%) showed mature sperm in wet preparation, whereas the sperm retrieval rate (SRR) of the patients with mosaic and non-mosaic KS was (57.1) % and (32.1) %, respectively. SR was significantly associated with testicular volume > 2 ml, total testicular volume > 5 ml and LH < 21.29 IU/L (p 0.007, 0.005, 0.044, respectively). FISH testing results showed that higher 46xy and lower 47xxy were significantly associated with successful sperm retrieval (p 0.014, 0.015, respectively). Rt and Lt testicular volumes, total testicular volume, LH and FISH could significantly predict successful SR. No statistically significant correlations were found between micro-TESE and age, serum FSH, serum TT, E2, prolactin. Further, receiver operation characteristic (ROC) curve showed Rt and Lt testicular volumes and total testicular volume and LH level and 46xy could significantly predict successful SR with p 0.007, 0.007, 0.005 and 0.044 and 0.015, respectively. Moreover, the cutoff point and sensitivity and specificity and positive and negative predictive values for Rt and Lt testicular volumes were as follows 2 ml, 73.1%, 61.4%, 52.78, 79.41, 2 ml, 76.9%, 57.8%, 51.28 and 80.65, respectively. While these values for total testicular volume were as follows 5.255 ml, 61.5, 75, 59.26 and 76.74, respectively. Furthermore, these values for LH and 46xy were as follows 17 IU/l, 73.1%, 50%, 46.34, 75.86, 16.35, 84.6, 50, 50 and 84.6, respectively. Conclusions Patients with mosaic KS had higher rates of SRR compared to non-mosaic KS.